The Firm as a Competent Team - Gunnar Eliasson (The Research Institute of Industrial Economics (IUI), 1988)
Results from empirical studies of firm behavior are synthesized into, a theory of the firm as a competent team. I demonstrate the existence of a tacit organizational competence exercising a leverage on the productivities of all other factors through selecting and allocating competent people, thus earning a monopoly rent in the capital market. The competence identified can only be fairly compensated through sharing in firm value growth in the equity market, exhibiting undervaluation of prime assets. Policies aimed at firm efficiency should improve the market measurement function, including stimulating insiders to exhibit information through trades.
Keywords: D24; L23; 330; Human capital; firm structure; factor compensation; efficiency